Salve Sant’Ana gloriosa: a ressignificação da festa e a produção do espaço urbano em Caicó/RN - Silvino, Marluce (2023)
Thinking about the organization of urban space through cultural practices, such as religious festivals, is the interpretation that this thesis carries out. These festivals have different approaches according to the scale of the place: in larger cities or metropolises they are presented in a totally different way from that revealed in the cities of the interior of the country, being, in the latter, often the event of greater social effervescence. The city of Caicó, in the interior of Rio Grande do Norte, Brazil, holds every year, at the end of July, the festivities in devotion to Sant’Ana, which gathers not only the city, but the entire region; even incorporates, in the touristic context, visitors from more distant places. The celebrations are anchored in the religious Catholic tradition that is the city's well-known mark, along with its cultural/traditional attributes, such as carne-de-sol, cheese and embroidery. When held, the festival impacts different aspects of society, not only in the Economics, with the flows of people and products, but also in the sociospatial structure of the place, that reorganizes itself to experience this moment. Aware of this, the objective of this work is to understand how the Festival of Sant’Ana is resignified with the passage of time and the developments in the spatial production of the city of Caicó by virtue of this phenomenon. he methodology is based on the triad of conceived, perceived and lived space, based on Lefebvre (2006), among Other classic authors, including Claval (2014), which supports the discussion about culture and geographic space. In the procedures we explore documentary research (from magazines, periodicals, local bibliographies) and empirical, with field observation and exploration of the object studied. In this context, it is stated that the historical construction of Caicó is linked to religiosity and the emergence of the Festival of Sant’Ana as landmarks that define the perception of the city. Over the years, those aspects consolidate themselves as the showcase for the local identity that reaffirms itself at each celebration.